Poslovno komuniciranje - Ferjan, Marko (2017)
Business Communication. »Who are we as an organization?« Organizational identity is the answer to the question. This book explores norms, needs, expectations and wishes from environment and the behaviours that bring solutions in the world of constant changes, high competition and need for constant development. From the beginning of modern buissness, the key for survival has always been communication, and it still is today. Communication is a process of exchanging verbal and non verbal messages. As a human body reacts to stimulations it gets thru feeling, seeing, smelling, tasting and hearing, so the organisation shoud have an awareness of the internal and external environment.  After detections from the physical world, the human brain develops perceptions, cognitions and emotions. In this process, the human body participates as a whole. Similarly, the communication of an organization should be considered as a whole. The content of business communication refers to all the attributes of the organization's identity. The forms of business communication are: interpersonal communication, marketing communication, public relations, investor relations, negotiations, lobbying and crisis communication; in context of organizational identity.
Keywords: business communication; organization; image; identity; perception